2021
DOI: 10.3390/metabo11100685
|View full text |Cite
|
Sign up to set email alerts
|

Defining Acute Coronary Syndrome through Metabolomics

Abstract: As an emerging platform technology, metabolomics offers new insights into the pathomechanisms associated with complex disease conditions, including cardiovascular diseases. It also facilitates assessing the risk of developing the disease before its clinical manifestation. For this reason, metabolomics is of growing interest for understanding the pathogenesis of acute coronary syndromes (ACS), finding new biomarkers of ACS, and its associated risk management. Metabolomics-based studies in ACS have already demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 171 publications
1
18
0
Order By: Relevance
“…The question of whether arterial and venous thrombosis are just two different clinical manifestations on the continuum of the same disease [ 49 ] remains to be answered. Plasma metabolomic studies from patients diagnosed with coronary syndrome identified upregulation of 2-OH-butyric acid, a glutathione presynthesis byproduct under hypoxia [ 50 , 51 ], in line with our findings of higher glutathione levels in RBCs from acute VTE patients. Purine metabolism has also been associated with unstable angina [ 52 , 53 ], metabolic syndrome and all-cause mortality [ 54 – 56 ], and venous thrombosis [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 87%
“…The question of whether arterial and venous thrombosis are just two different clinical manifestations on the continuum of the same disease [ 49 ] remains to be answered. Plasma metabolomic studies from patients diagnosed with coronary syndrome identified upregulation of 2-OH-butyric acid, a glutathione presynthesis byproduct under hypoxia [ 50 , 51 ], in line with our findings of higher glutathione levels in RBCs from acute VTE patients. Purine metabolism has also been associated with unstable angina [ 52 , 53 ], metabolic syndrome and all-cause mortality [ 54 – 56 ], and venous thrombosis [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 87%
“…To improve management and therapy of ACS, effective tools for risk assessment in secondary prevention are needed. Since ACS frequently exhibits metabolic alterations, a metabolomics approach might play a significant role in the better management of ACS patients, by advancing our understanding of the mechanisms underlying the increased risk of recurrent cardiovascular events following ACS and helping in the identification of biomarkers related to these adverse events [4].…”
Section: Introductionmentioning
confidence: 99%
“…Prognostic classification in patients admitted with ACS is necessary for providing efficient follow-up and guiding treatment. During the last years, many efforts have been made to identify predictive biomarkers for adverse outcomes following ACS ( 2 ) and metabolomics seems a promising approach ( 3 ).…”
Section: Introductionmentioning
confidence: 99%